Optimalisasi Komunikasi Publik: Analisis Proses Penulisan dan Publikasi Berita di IKP Diskominfo Kota Bukittinggi - Putri, Selsabila; Suparman (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This article discusses the process of writing and publishing news in the Information and Public Communication (IKP) division of Department of Communication and Informatics (Diskominfo) Bukittinggi City. This descriptive qualitative research was conducted over four months from January to May 2025. The results show that IKP Diskominfo Bukittinggi CIty serves as the main channel for city government news. The news writing process begins with data collection, event coverage, and processing into narratives, flyers, and videos. The narrative writing follows journalistic principles with 5W+1H elements, comprehensively explaining activities including attending leaders and involved parties. The validity of data is the most crucial aspect in all news reporting processes. Publication is done through the official government website and government social media such as Instagram, Facebook, and YouTube. There are slight differences in the narratives published on the website and social media. Finalization and monitoring are carried out to minimize errors, with quick corrections if mistakes occur after publication.